A new subgenus and two new species of oribatid mites of the genus Neoribates (Acari, Oribatida, Parakalummidae) from the Philippines - Ermilov, Sergey G.; Corpuz-Raros, Leonila (Zootaxa, 2015)
The oribatid mite family Parakalummidae (Oribatida, Oripodoidea) is recorded for the first time from the Philippines. A new subgenus of the genus Neoribates, N. (Pseudoneoribates) subgen. nov., is proposed and two new species, N. (Ps.) negrosensis sp. nov. and N. (Ps.) kontschani sp. nov., are described. The new subgenus differs from the other subgenera and genera of Parakalummidae by the morphology and structure of prolamellae, which are smoothly fused to lamellae basally and curving backwards in medio-anterior parts. An identification key to all known subgenera of Neoribates is given. Neoribates (N.) corticis (Ewing, 1913) combined in the subgenus Neoribates (Parakalumma): N. (Par.) corticis comb. nov..